The expectations hypothesis of the term structure of interest rates: Evidence from the Fourier cointegration test - (:unkn) unknown (Peter Lang AG, 2019)
The expectation hypothesis of the term structure of interest rate implies that long term interest rates should reflect future short term changes. The main purpose of this study is to investigate the Expectations Hypothesis of term structure in France by using Fourier cointegration test. Fourier cointegration test to accommodate possible structural changes of unknown form in the deterministic term without estimation of the break dates, the number of breaks, and the form of breaks. According to the results obtained from this analysis, the expectation hypothesis of the term structure of interest rate does not hold for France. © Peter Lang AG 2019.
Keywords: Expectation hypothesis; Fourier cointegration test; Fourier stationarity test